Defining Digital Literacy in the Age of Computational Propaganda and Hate Spin Politics - Salma, Aqida Nuril (KnE Social Sciences, 2019)
In this era, people’s lives are intertwined with the Internet and digital media although society might have to bear potential negative effects of these platforms. Free flow of information and the rise of hate speech, fake news and disinformation on the Internet have no doubt increased social polarization. Furthermore, a new phenomenon has arisen, which combines hate speech with indignation or offence-taking, and that is hate spin. Hate spin uses hate speech and fake news as a weapon to gain access to political power. Hate spin is considered to be one of the biggest threats to any democratic country, including Indonesia. A relatively young democracy and its reputation for religious moderatism and diversity, Indonesia has not been immune to the hoax epidemic plaguing societies around the world recently. Scholars assume that improving digital literacy is the best solution against hate spin in Indonesia. However, the current concept of digital literacy has been limited as merely a matter of technical skill. This paper offers an analysis on how to define the contemporary digital literacy concept that has moved beyond basic Internet access, and on how the technology works and is used by political elites with evidence of computational propaganda delivered through political bots, fake accounts and false news during recent political events in Indonesia. Keywords: digital literacy, computational propaganda, hate spin, Internet, politics